Exposure to Perfluoro-Octanoic Acid Associated With Upstream Uncoupling of the Insulin Signaling in Human Hepatocyte Cell Line - De Toni, Luca; Di Nisio, Andrea; Rocca, Maria Santa; Guidolin, Diego; Della Marina, Alice; Bertazza, Loris; Sut, Stefania; Purpura, Edoardo; Pannella, Micaela; Garolla, Andrea; Foresta, Carlo (Frontiers in Endocrinology, 2021)
Perfluoro–alkyl substances (PFAS) are chemical pollutants with prevalent stability and environmental persistence. Exposure to PFAS, particularly perfluoro-octanoic acid (PFOA), has been associated with increased diabetes-related cardiovascular mortality in subjects residing areas of high environmental contamination, however the exact pathogenic mechanism remains elusive. Here we used HepG2 cells, an in vitro model of human hepatocyte, to investigated the possible role of PFOA exposure in the alteration of hepatic glucose metabolism. HepG2 cells were exposed for 24 hours to PFOA at increasing concentration from 0 to 1000 ng/mL and then stimulated with 100 nm Insulin (Ins). The consequent effect on glycogen synthesis, glucose uptake and Glut-4 glucose transporter translocation was then evaluated by, respectively, Periodic Acid Schiff (PAS) staining, 2-deoxyglucose (2-DG) uptake assay and immunofluorescence. Exposure to PFOA was associated to reduced glycogen synthesis and glucose uptake, at concentration equal or greater than, respectively, 0,1 ng/mL and 10 ng/mL, with parallel impaired membrane translocation of Glut-4 upon Ins stimulation. Western blot analysis showed early uncoupling of Insulin Receptor (InsR) activation from the downstream Akt and GSK3 phosphorylation. Computational docking analysis disclosed the possible stabilizing effect of PFOA on the complex between InsR and GM3 ganglioside, previously shown to be associated with the low grade chronic inflammation-related insulin resistance. Consistently, long term treatment with glucosyl-ceramide synthase inhibitor PDMP was able to largely restore glycogen synthesis, glucose uptake and Glut-4 translocation upon Ins stimulation in HepG2 exposed to PFOA. Our data support a novel pathogenic mechanism linking exposure to PFOA to derangement of hepatocyte cell metabolism.